?LIPID COMPONENTS FROM THE SEEDS OF SAPINDUS MUKOROSSI L (Biological Sciences - PJSIR, 1999)
Seed lipids of Sap indus mukorossi L. were classified and fatty acid composition was determined. The fatty acid composition of the total lipids was C12•1 (0.3%), C14•0 (traces), C16•0 (4.6%), CIS•O (traces), C20•0 (3.5%), CIX•I (56.0%), C18 • 2 (5.8%), C18 • 3 (1.4%) and C20:1 (28.4%). The hydrocarbon fraction contained main components pentacosane C25HS2 with 11.75%and hentriacontane C3IH64 with 17.20%.Odd number It-alkaneswere predominant (70.95%).